Behaviour and design of composite columns incorporating compact high-strength steel plates. (April 2015) - Aslani, Farhad; Uy, Brian; Tao, Zhong; Mashiri, Fidelis
Abstract: Concrete filled steel tubular columns (CFSTCs) are finding increasing use in modern construction practice throughout the world. The efficiency of CFSTCs can be further improved if high-strength materials are used. High-strength steel provides attractive alternatives to normal-strength steel for multi-storey and high-rise construction applications. This paper presents an extensive experimental investigation into the axial load behaviour of square composite columns incorporating compact high-strength steel plates. The test parameters include the concrete strength ( f ′ c  = 21–55 N/mm 2 ), depth-to-thickness ratios in the range of 16–40, as well as length-to-depth ratios in the range of 2.60–2.85. Furthermore, a simplified confining pressure versus depth-to-thickness ratio model, appropriate confined concrete constitutive models, and an accurate finite element model which incorporates the effects of initial local imperfections and residual stresses has been developed using the commercial program ABAQUS. The predictions of the behaviour, ultimate strengths, and failure modes are compared with the experimental results to verify the accuracy of the models developed. Additionally, comparisons with the prediction of axial load capacity by using the Australian Standards, Eurocode 4, and American Institute of Steel Construction code provisions for composite columns are also carried out. Highlights: Developed simplified confining pressure model for high-strength square CFST columns Developed confined concrete maximum compressive strength model for CFST columns Developed accurate FEM model for high-strength square CFST columns